DEMOKRASI DALAM NEGARA AGAMAIS Hubungan antara demokrasi dengan agama dalam pembentukan negara demokratis yang ideal - Nujartanto, Antonius Baju (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2019)
Democracy is a term which is understood as polical matters. Every nation owns his policy to maintain the practice of a democracy. Particulary in Indonesie, actualy we live our own democracy as a way of life that is based in our political, cultural and sosial’s background. Start from this point of view, we must put our understanding of democracy properly, then the rights of every citizen could have its place. In the other side we put the importance of the religious consciousness in this activity of democracy that rises some particular problemes. This is the point central of this discussion that we want to make it clear.